Modulation of cellular cholesterol alters P-glycoprotein activity in multidrug-resistant cells - Troost, Joachim; Lindenmaier, Heike; Haefeli, Walter E.; Weiß, Johanna (Molecular pharmacology, 2004)
The drug transporter P-glycoprotein (ABCB1) plays an important role in drug distribution and elimination, and when overexpressed it may confer multidrug resistance (MDR). P-glycoprotein is localized in the plasma membrane, especially within rafts and caveolae, characterized as detergent-resistant membranes (DRMs). This study investigated the effect of cholesterol depletion and repletion as well as saturation on subcellular localization and function of P-glycoprotein to determine the effect of DRM localization on P-glycoprotein-mediated drug efflux. In L-MDR1 overexpressing human P-glycoprotein, cholesterol depletion removed P-glycoprotein from the raft membranes into non-DRM fractions, whereas repletion fully reconstituted raft localization. P-glycoprotein function was assessed by realtime monitoring with confocal laser scanning microscopy using BODIPY-verapamil as substrate. Cholesterol depletion reduced P-glycoprotein function in L-MDR1 cells resulting in intracellular substrate accumulation (159% ± 43, p < 0.001; control = 100%). Cholesterol repletion reduced intracellular substrate fluorescence (120% ± 36, p < 0.001) and restored the transporter activity. Addition of surplus cholesterol (saturation) even enhanced drug efflux in L-MDR1 cells, leading to reduced intracellular accumulation of BODIPY-verapamil (69% ± 10, p < 0.001). Transport of BODIPY-verapamil in cells not expressing human P-glycoprotein (LLC-PK1) was not susceptible to cholesterol alterations. These results demonstrate that cholesterol alterations influence P-glycoprotein localization and function, which might contribute to the large interindividual variability of P-glycoprotein activity known from in vivo studies.
Gesehen am 19.05.2021